POLITICAL COMMUNICATION OF HM. RIDWAN KAMIL AND DEDDY MIZWAR WITH POLITICAL PARTIES - Adiyana Slamet, Dadang Rahmat Hidayat, Dede Mariana, Karim Suryadi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The purpose of this study is to analyze holistically and in-depth about the political communication process of HM Ridwan Kamil and Deddy Mizwar with Political Parties in the nomination process of the simultaneously direct regional election of West Java governor in 2018, political communication reality and political communication activities of HM Ridwan Kamil and Deddy Mizwar with Political Parties in the nomination process of the simultaneously direct regional election of West Java governor in 2018. This research used qualitative approach with a case study method that is holistic. Data collection was conducted through interviews, records, observations, documentation, archives, physical devices, and literature studies. There are 14 informants, determined by purposive technique. Data analysis was conducted based on theoretical propositions of political communication and developed a case description framework. The results showed that political communication of HM Ridwan Kamil and Deddy Mizwar with Political Parties in the simultaneously direct regional election of West Java governor in 2018 involved a third political communication actor (non-party) as a "bridge" to conduct political communication with political communication actors from political parties, both HM Ridwan Kamil and Deddy Mizwar showed up religious and nationalist symbols, using hybrid media to win the "hearts" of political party elites to gain political capital in the form of recommendation support as a candidate for governor. The reality of political communication that occurs to the governors candidates makes the basic capital (survey results) as a bargaining power and bargaining position with political party elites which raises political pragmatism, strengthened political oligarchy in the process of determining governor candidates conducted by political party elites.